Functional Magnetic Resonance Image (FMRI) Based Brain Activity Classification - Far, Mehran Sahandi (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ)., 2013)
Functional Magnetic Resonance Imaging (FMRI) is a powerful tool to predict the current activity in the human brain. With the help of machine learning tools, the cognitive function of the human brain can be automatically classified into two or more states by analyzing the FMRI images. In this thesis, the main goal is to design an automated system to predict whether a given subject is viewing a picture or a sentence. A dataset of six subjects is considered for this purpose. Two classification schemes, namely support vector machines (SVM) and nearest neighbor classifier (NN) are used. Due to the high dimensionality of the FMRI data, feature selection is generally considered. In order to reduce the feature dimensionality, four reduction methods, namely region of interest (ROI), N-most active voxels, ROI average and N-most active voxels within ROI are studied. Both subject dependent and subject independent experiments are conducted where the former studies the categorization problem separately for each subject and the latter does not use the tested subject during training. Experimental results have shown that SVM provides better scores compared to NN approach and selecting N-most active voxels within the ROI provided the best scores, verifying the importance of applying feature selection in this domain.…………………………………………………………………………… ÖZ: Fonksiyonel Manyetik Rezonans Görüntüleme (FMRG) insan beyninde şu andaki aktiviteyi tahmin etmek için güçlü bir araçtır. Makineye dayalı öğrenme araçları yardımıyla insan beyninin bilişsel fonksiyonu iki veya daha fazla durumdan birine FMRG görüntüleri incelenerek otomatik olarak sınıfladırılabilmektedir. Bu tezde, esas amaç bir kişinin bir resime veya bir cümleye bakmakta olduğunu ayırt edecek otomatik bir sistem tasarlamaktır. Bu amaçla altı kişi içeren bir verikümesi kullanılmıştır. Destek vectör makinaları (DVM) ve enyakın komşu (EK) olmak üzere iki sınıflandırıcı kullanılmıştır. FMGR verisinin yüksek boyutlu olmasından dolayı genellikle öznitelik seçimi uygulanmaktadır. Öznitelik boyunun azaltılması için İlgi Alanı (İA), N-En aktif voxel, İA ortalama ve İA içerisindeki N-En aktif voxel olmak üzere dört farklı yöntem denenmiştir. Kişiye bağlı ve kişiden bağımsız deneyler yapılmış olup, ilkinde sınıflandırma promlemi her kişi için ayrı olarak çalışılmış, ikincisinde ise test edilen kişi eğitme verisi içinde yer almamıştır. Deneysel sonuçlar DVM yaklaşımının EK'ya göre daha başarılı sonuçlar verdiğini, İA içerisindeki N-En aktif voxel seçiminin de eniyi başarımı sağladığını göstermiş ve bu alanda öznitelik seçmenin önemini onaylamıştır.
Master of Science in Computer Engineering. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Engineering, Dept. of Computer Engineering, 2013. Supervisor: Prof. Dr. Hakan Altınçay.
Keywords: Computer Engineering; Brain - Magnetic resonance imaging - Cognitive neuroscience; Magnetic Resonance Imaging - Brain Mapping; Biomedical Engineering; Medical instruments and apparatus; Functional Magnetic Resonance Imaging, Cognitive State Decoding, Feature Selection, Support Vector Machines, Nearest Neighbor Classifier